Supramolecular gel-phase materials with advanced functions - Irwansyah (2014)
Fabrication of new surapmolecular gel-phase materials based on selfassembly of low molecular weight gelator is motivated by potential applications of supramolecular gels in diverse fields. These types of materials have found application in field of biomaterial, electronic, sensing, and template for inorganic synthesis. However, most of low molecular gelator reported required complexes design and multi steps covalent practices. Hence, simple design and synthesis but at the same time posses advance functions are needed for fabrication supramolecular gel. In this thesis, firstly we reported a low molecular weight organogelators (LMWOGs) based on Fmoc-amino acid for multi purposed application. The gelator, Fmoc-lys(boc)-C16 was synthesized by one step coupling between amino acid bearing chromophore, Fmoc-lys(boc)-OH, and hexadecylamine. The gelator form stable transparent gel in cyclohexane and hexane with ultralow minimum gelation concentration (MGC) due to the cooperative formation of hydrogen bond and of π-π stacking of Fmoc moiety as indicated by fourier transform infrared spectroscopy (FTIR), fluorescence and circular dichroism (CD) study. Field emission scanning electron microscopy (FESEM) image revealed that gels consist of 1D self-assembly fibrous network. We demonstrated that Fmoc-lys(boc)-C16 selectively gelate organic solvent from their mixture in water. We also reported an efficient energy transfer between fluorenyl and dansyl moeities within self-assembled organogel. Energy transfer study indicate that the addition of acceptor group (octyl dansyl) decrease the emission of Fmoc group within the gel phase. Concentration dependent study revealed that high efficiency energy transfer (~89%) between Fmoc and Dansyl was achieved in gel phase. Moreover our study also shown that inclusion of 3% acceptor causes 50% quenching of donor that make Fmoc-Dansyl system as an ideal light harvesting system. As a multi purpose organogel, we also demonstrated that Fmoc-lys(boc)-C16 gel was able to remove organic dye from solution with high efficienty (~94%). In the second works, the formation of supramolecular hydrogel via ultra simple and facile approach using Fmoc-amino acid as building block was described. Fmoc-phenylalanine (F) was the smallest Fmoc-amino acid as building block for self-assembly into hydrogel. Our systematic studies revealed that molecular arrangement of F in self-assembly structure was driven by π-π stacking of Fmoc group and H-bond. In addition, the intermolecular interactionwas stabilized by the presence of phenyl group stacking. Furthermore, to fabricate straight forward strategy for antimicrobial supramolecular hydrogel, we described a facile route for antimicrobial hydrogel without involving expensive and time consuming covalent practices. The incorporation of Fmoc-leucine (L) into F hydrogel results in antimicrobial supramolecular hydrogel that able to kill bacteria pathogen S. aureus with fast killing rate.